(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
One of the major plastic producers in Asia is the Philippines. High-density polyethylene (HDPE) is one of the major pollutants and can be seen from the land to the ocean. Concrete, however, is present everywhere you go from the roads, to the skies, and the seas. The researchers of this study had an idea to add HDPE to plastics to its extent to widen the plastic recycling opportunity nationwide. The quantitative research method was used as the research design for the study while using the experimental research method to gather the result through a machine in determining the bricks’ compressive strength, water absorption, and moisture content. A 300 Series Electromechanical Universal Testing Machine was used to determine the compressive strength of the bricks, while a discrete observation and manual submersion of the bricks were used to determine its water absorption and moisture content. The results showed that with the increase in HDPE content in concrete, compressive strength decreases over time. The first treatment passed the recommended psi of standard concrete. The second treatment lies between the average psi, and the last barely hands on the minimum requirement. The amount of water absorbed and the moisture content of the bricks lies between the making of the concrete brick. The brick should be as perfect as possible to reduce the number of air pockets and holes to prevent water from seeping through. Based on the results, the difference between the ASTM C129 standard and the HDPE brick was significant, but the difference between and among the structure of the concrete bricks was not significant given that it has different treatments. The problems encountered by the researchers did not hinder the construction of the experiment. The suggestions and recommendations given by the engineers are essential to further improve the concrete. A 20% HDPE concrete brick is significantly better than the standard non-load-bearing brick. The HDPE content should be minimized to increase the compressive strength and remediate the process of making the bricks to decrease the percentage of water absorption and moisture content. The bricks should exceed the standard ASTM C129 of 500 psi and should not fall below 500 psi. The amount of HDPE content in the concrete brick should vary and should not be fractionalized but randomized. The plastic should be gathered beforehand, and possible sources and sponsorships for the HDPE wastes and plastic shredders should be found to reduce the production cost as much as possible.